Artificial Intelligence’ Receptiveness for Inclusive Education at Obafemi Awolowo University, Nigeria - Temitope, Oteyola Adetokunbo; Oyetola, Oyeniran; Makinde, Babatunde Folorunso (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The challenges of teaching students with disabilities in Nigeria include inadequate teachers, a deficiency in the integration of technology into classroom instruction, and poor information technology infrastructure, among others. Special schools, which are dedicated to special needs students, also cannot adequately cater for them. Inclusive education provides the desired opportunities to navigate some of these challenges and prevent underserved discrimination against this group of students. The use of AI-mediated platforms has been found effective in teachers’ preparation for inclusive education in some other climes. This study investigated preservice teachers’ receptiveness and the influence of sex on the usability of AI for inclusive education. The study adopted a post-test-only experimental design. Forty-five students that participated in the training organized for the integration of the AI-mediated platform for teaching practice at Obafemi Awolowo University, Ile Ife, Nigeria, were sampled for the study. The simSchool Survey Questionnaire (SSSQ) was used for data gathering. Analysis of data showed that preservice teachers were highly receptive to the usability of the platform in teachers’ preparation for inclusive education (mean score image = 22.46). Analysis of data also showed that sex has no significant influence on the preservice teachers’ receptiveness (F (1,43) = 0.73; p > 0.05).